2017
DOI: 10.1111/evo.13187
|View full text |Cite
|
Sign up to set email alerts
|

Trpc2 pseudogenization dynamics in bats reveal ancestral vomeronasal signaling, then pervasive loss

Abstract: Comparative methods are often used to infer loss or gain of complex phenotypes, but few studies take advantage of genes tightly linked with complex traits to test for shifts in the strength of selection. In mammals, vomerolfaction detects chemical cues mediating many social and reproductive behaviors and is highly conserved, but all bats exhibit degraded vomeronasal structures with the exception of two families (Phyllostomidae and Miniopteridae). These families either regained vomerolfaction after ancestral lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 98 publications
(238 reference statements)
1
54
0
Order By: Relevance
“…The inactivation of Trpc2 has previously been associated with a nonfunctional VNO. With our study, we confirm and extend these previous findings that Trpc2 was inactivated in catarrhines, cetaceans and several bats (Liman & Innan, ; Yohe et al, ; Yu et al, ). Our screen further showed that Trpc2 is inactivated in the aquatic manatee ( Trichechus manatus ) that also lacks a functional VNS.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The inactivation of Trpc2 has previously been associated with a nonfunctional VNO. With our study, we confirm and extend these previous findings that Trpc2 was inactivated in catarrhines, cetaceans and several bats (Liman & Innan, ; Yohe et al, ; Yu et al, ). Our screen further showed that Trpc2 is inactivated in the aquatic manatee ( Trichechus manatus ) that also lacks a functional VNS.…”
Section: Resultssupporting
confidence: 92%
“…The VNS was lost in the entire catarrhine and cetacean lineages. We estimated that a functional VNS was lost at least twice independently in Chiroptera, once in the common ancestor of Pteropodidae and independently in the common ancestor of Vespertilionidae, though this number maybe higher based on recently published studies that investigated many additional bat species (Yohe et al, ; Yohe & Davalos, ). The fifth independent loss of the VNS occurred in the fully aquatic Sirenia lineage, which is represented in our analysis by the manatee ( Trichechus manatus ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their feeding strategies are exceptionally diverse among mammals, including insects, vertebrates, fruit, pollen, nectar, young leaves, and even blood (Ferrarezi and Gimenez 1996;Freeman 2000;Wetterer et al 2000;Giannini and Kalko 2004;Gardner 2007;Baker et al 2012). This diversity is reflected in their morphology, and their impressive cranial diversity provides an excellent system for investigating the evolution of complex phenotypes (Nogueira et al 2009;Nogueira 2010, 2011;Santana et al 2010Santana et al , 2012Dumont et al 2011Dumont et al , 2014Pedersen and Müller 2013;Rossoni et al 2017;Yohe et al 2017Yohe et al , 2018.…”
mentioning
confidence: 99%
“…Similar loss of function in short-wave opsin visual genes has been found in bats with advanced echolocation capabilities (30). Bats have undergone the most extensive loss of function of the pheromone-detecting vomeronasal system compared with any other mammalian group (68)(69)(70), offering an opportunity to better understand the process of sensory vestigialization and the vomeronasal loss seen throughout mammals, including humans. Therefore, studying the evolution of these genes and genomic regions in bats-the sensory specialists-will elucidate how the mammalian genome has responded to past evolutionary pressures driven by changing environmental conditions.…”
Section: Model For the Evolution Of Sensory Perceptionmentioning
confidence: 75%